Microwave assisted growth of stannous ferrite microcubes as electrodes for potentiometric nonenzymatic H2O2 sensor and supercapacitor applications - K., Bindu; Sridharan, Kishore; K. M., Ajith; Lim, Hong Ngee; Nagaraja, Hosakoppa S. (Elsevier, 2016)
Electrochemical sensors and supercapacitors are two noteworthy applications of electrochemistry. Herein, we report the synthesis of SnFe2O4 microcubes and Fe2O3 nanorods through a facile microwave assisted technique which are employed in fabricating the electrodes for nonenzymatic hydrogen peroxide (H2O2) sensor and supercapacitor applications. SnFe2O4 microcubes exhibited an enhanced specific capacitance of 172Fg−1 at a scan rate of 5mVs−1 in comparison to Fe2O3 nanorods (70Fg−1). Furthermore, the H2O2 sensing performance of the fabricated SnFe2O4 electrodes through chronopotentiometry studies in 0.1M PBS solution (at pH 7) with a wide linear range revealed a good sensitivity of 2.7mVμM−1μg−1 with a lowest detection limit of 41nM at a signal-to-noise ratio of 3. These results indicate that SnFe2O4 microcubes are excellent materials for the cost effective design and development of efficient supercapacitors as well as nonenzymatic sensors.